Antimicrobial Activity of Paw-paw (Carica papaya) Leaves and Seed Extracts on Shigella and Salmonella Species - Brown, Samuel Tamunoiyowuna Cockeye; Mohammed, Ikrimah Usman; Umaru, Isaac John (Darul Yasin Al Sys, 2024)
This study investigates the antimicrobial properties of ethanolic and aqueous extracts of Carica papaya leaves and seeds against Salmonella spp. and Shigella spp. The extracts were evaluated for their antibacterial activity using the agar well diffusion method, with zones of inhibition measured to assess efficacy. Results revealed that the ethanolic extract of Carica papaya leaves exhibited significant antibacterial activity against Salmonella spp., with a zone of inhibition of 14 mm at a concentration of 200 mg/mL, whereas no activity was observed against Shigella spp. The aqueous extracts, as well as both types of extracts from the seeds, showed no significant antibacterial effects against the tested organisms. The study highlights the superior extraction capability of ethanol over water for bioactive compounds and suggests potential therapeutic applications for Carica papaya extracts in treating Salmonella infections. However, further research is needed to explore higher concentrations and isolate specific active compounds. This work supports the traditional medicinal use of Carica papaya and indicates its potential as a source of new antibacterial agents.